AGAMA DAN SOLIDARITAS SOSIAL - Mohammad Isfironi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
Modern live not always change social behavior be individual. Howeveron the contrary give us a loyalty to traditional tenet that havecommunal characteristic. Traditional festival of Rasulan in GunungKidul Region suspicion that solidarity are preference of people in spiteof the world has change. Mechanic solidarity be strong background ofPopularity of this tradition in whole region.Rasulan tradition are respons of people on Gunung Kidul aboutmodernization process that disposed neglect and disparage intimateinteraction both people in public sphere that more and more limited.In a functional manner, the tradition that namely as ‘selametan’ havetraditional and religion motives. Plant and harvest period are twoimportant momentum by farmer people in Gunung Kidul. First, that isa certain that need to thank God and second as modesty expression.Rasulan tradition done alike party or festival that beginned prayer thatlead by Imam. In many place done more big, even was agenda bytourism official duty of Gunung Kidul Regency. Another, done byfamilies and them relative brother with replacement. Rasulan havebeen popular tradition with offering motive for destination is in orderthat avoided from danger live and confirm social solidarity.By rasulan tradition we can obtained meaning an social intelligent onresponse about aroud environment change that be able threaten socialexistence and social order harmoy without reject social change thatimpossible to avoided.